Do Fiscal Rules Constrain Fiscal Policy? A Meta-Regression-Analysis - Friedrich Heinemann; Marc-Daniel Moessinger; Mustafa Yeter (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Numerical fiscal rules are implemented to counterbalance the deficit bias in budgetary policy. Over the recent years, an increasing number of studies try to test the actual effectiveness of fiscal rules. This meta-analysis condenses the existing evidence from different regional and federal contexts. It explores the study characteristics which are associated with different findings. Based on a preliminary analysis and a still incomplete sample of primary studies, the results point to a consensus that fiscal rules indeed constrain fiscal policies. This result also appears to hold in light of the criticism that rules are the endogenous reflection of fiscal preferences: even studies with a comprehensive control for fiscal preferences do not lead to systematically weaker levels of statistical significance.
Keywords: H61; H74; H69; 330